TRANSMISSIBLE VENEREAL TUMOR SURGERY AND CHEMOTHERAPY IN A FEMALE LOCAL DOG WITH A HISTORY OF MACROCYTIC-HYPOCHROMIC ANEMIA - Lutviana, An'nisafitri; Sudisma, I Gusti Ngurah; Wandia, i Nengah (Buletin Veteriner Udayana; Vol. 15 No. 4 August 2023, 2022)
Canine transmissible venereal tumor (CTVT) is a malignant tumor of the genital organs that is transmitted to dogs through implantation of tumor cells in the mucous membranes during mating, licking, biting, fighting, or various forms of direct contact. The case animal is a 1.5 years old female local dog with a body weight of 10.45 kg with a complaint of a lump in the vaginal area for the last 2 months and blood dripping from her vagina. Based on anamnesis, physical examination, and supporting examinations including hematological examination, it was found that the case dog had hypochromic macrocytic anemia, on cytology examination found the presence of intranuclear and intracytoplasmic CTVT vacuoles, and histopathological examination revealed homogeneous lymphoblasts and lymphocytes, mitotic cells, and connective tissue stroma, so the case dog was diagnosed with Canine Transmissible Venereal Tumor. Treatment for CTVT is done through surgery and chemotherapy. Preoperatively given atropine sulfate premedication at a dose of 0.02 mg/kg BW subcutaneously, and anesthetized using a combination of ketamine-xylazine at a dose of 2 mg/kg BW and 12 mg/kg BW intravenously, respectively. Surgery is performed by excision of the tumor mass in the vaginal area. Postoperatively, cefotaxime at a dose of 25 mg/kg BW was administered intravenously twice a day and the analgesic tolfenamic acid at a dose of 4 mg/kg BW was administered intramuscularly once a day. Followed on the second day by administering the drug orally, namely the antibiotic cefixime at a dose of 5 mg/kg BW given twice a day for five days, meloxicam at a dose of 0.1 mg/kg BW given once a day for five days. Sangobion capsules are given once a day for five days. Dogs were given chemotherapy drug vincristin sulfate at a dose of 0.025 mg/kg BW intravenously on the 4th and 11th postoperative days. On the fourth postoperative day, the vulva did not experience swelling, the dog was actively playing, normal urination, eating and drinking well, no disturbances occurred, so the case dog was declared to have developed well after surgery.